Predictors of flood preparedness among youth in the east coast region, malaysia - Mohd Rozaimy, Ridzuan (2024)
Climate change has increased the vulnerability of the global community to natural hazards, including flooding. Youth are considered one of the most vulnerable groups of people, especially in the event of a disaster. Compared to the average Malaysian youth, youth in the East Coast states (Terengganu, Kelantan and Pahang) are disproportionately affected by environmental and climatic hazards. Youth in these states are more likely to have experienced flooding than the average Malaysian youth. Many deaths related to Malaysian youth have been reported from the east coast states of Peninsular Malaysia. Integrating two theories— the Theory of Planned Behaviour and the Health Belief Model — this study examines the predictors associated with flood-related behaviours among youth in the East Coast region. Using purposive sampling, a total of 350 respondents participated in this study. Structural equation modelling (SEM) using Smart-PLS version 4.0 was used to test the relationships between the constructs in this study. The study found that attitude, subjective norms, perceived susceptibility, and perceived severity showed a positive relationship with flood preparedness intention, whereas past flood experience showed a significant relationship and perceived behavioural control did not show a significant relationship with flood preparedness intention. This study also found that perceived behavioural control and flood preparedness intention were positively related to flood preparedness behaviour. Interestingly, except for perceived behavioural control, community participation positively moderated the relationship between attitude, subjective norms, perceived susceptibility, perceived severity and flood preparedness intention. Community participation was also found to have a moderating effect on the relationship between past experience and flood preparedness intention. However, trust in public protection did not moderate the relationship between flood preparedness intention and flood preparedness behaviour. This study contributes to the body of knowledge on flood disaster preparedness behaviour in Malaysia. It can also serve as a starting point for future researchers to determine flood preparedness intention and behaviour and stimulate new research that involves modifying and improving the model through continuous testing. The study also provides valuable insights for policy makers and government agencies, particularly NADMA and youth organisations, to develop targeted interventions and strengthen flood preparedness among youth in the East Coast region to ultimately promote resilience and mitigate the impact of future flood events.